PCR Results of Vector and Carrier Investigations for the Presence of Tick-Borne Borreliosis, Human Monocytic Ehrlichiosis, and Human Granulocytic Anaplasmosis Agents in Natural Foci of the Rostov Region - L. V. Romanova; I. V. Dvortsova; E. A. Moskvitina; T. N. Borodina; N. L. Pichurina; A. P. Savchenko; M. V. Zabashta; I. V. Orekhov; A. V. Zabashta (Проблемы особо опасных инфекций, 2017)
Objective of the study is to detect the circulation of the agents of ixodic tick-borne borreliosis (ITB), human monocytic ehrlichiosis (HME), and human granulocytic anaplasmosis (HGA) in samples collected from carriers and vectors of transmissible tick-borne infections using PCR-assay. Materials and methods. Field material was studied in PCR for evaluating the rate of infection by causative agents of tick-borne infections (tick-borne borrelioses, ehrlichioses, anaplasmosis) in combined natural foci on the territory of the Rostov Region. Results and conclusions. The data obtained during epizootiological investigations carried out in 21 administrative districts and 10 cities of the Rostov Region between 2014 and 2016 were used in the study. The results were indicative of spontaneous infection in ixodic ticks by ITB causative agent on the territory of the Rostov Region, as well as of presence of corresponding natural focus. Since 2013 the activity of different components of ITB natural focus was confirmed by the detection and official registration of patients. Moreover, in the Rostov Region for the first time ever the circulation of HME and HGA causative agents was recorded and territorially combined foci of HME and HGA with ITB were identified. The results obtained allow assuming the genesis of a focus of ixodic tick-borne borreliosis and monocytic and granulocytic ehrlichioses owing to annual expansion of the areal of ticks, infected by these pathogens, and animals on which the ticks are feeding. PCR-analysis is of significant value for assessment of spread of causative agents of the “tick-borne” infections in the Rostov Region, forecasting of epidemiological situation, as well as implementation of preventive measures in the region.